L1CAM Is Not a Predictive Factor in Early-stage Squamous-cell Cervical Cancer - Romanová, Martina; Židlík, Vladimír; Javůrková, Veronika; Kondé, Adela; Šimetka, Ondřej; Klát, Jaroslav (In vivo (Athens, Greece), 2023)
AIM: Our study aimed to assess expression of L1 cell adhesion molecule (L1CAM) in early-stage cervical squamous-cell cancer as a prognostic factor. PATIENTS AND METHODS: This retrospective, single-institution study included 154 patients who underwent radical hysterectomy for early-stage squamous cell cervical cancer between 2007 and 2017. Tumor samples from 154 patients were available for L1CAM analysis by immunohistochemistry. Among all patients, radical abdominal hysterectomy was performed in 144 cases. RESULTS: L1CAM expression was positive in 24 tumors (15.6%) of the whole group. In relation to the grade of differentiation and the presence of lymphovascular invasion, L1CAM expression did not show an association (p=0.154 and p=0.306, respectively). The disease-free interval and overall survival also did not significantly differ between L1CAM-positive and L1CAM-negative cases (p=0.427 and p=0.240, respectively). For histopathological characteristics, L1CAM-positive cases had a significantly higher median tumor size (p=0.015). Even in the selected group of 115 cases without nodal infiltration, L1CAM status had no effect on the relapse rate during follow-up. CONCLUSION: Our study did not confirm the results of previous studies showing L1CAM expression to be a negative prognostic factor in cervical cancer. In our study, increased L1CAM expression in early-stage squamous-cell cervical cancer was not associated with adverse prognosis regarding disease recurrence, disease-free survival, nor overall survival. L1CAM expression was correlated only with the size of the tumor.
Keywords: Humans; Biomarkers, Tumor; Female; nádory děložního čípku; L1 cell adhesion molecule; lidé; Neural Cell Adhesion Molecule L1; early stage; prognostic factor; nádorové biomarkery; staging nádorů; ženské pohlaví; Retrospective Studies; prognóza; molekula buněčné adheze nervové L1; Uterine Cervical Neoplasms; spinocelulární karcinom; retrospektivní studie; Carcinoma, Squamous Cell; lokální recidiva nádoru; Neoplasm Staging; squamous-cell cervical carcinoma; Neoplasm Recurrence, Local; Prognosis